(untitled) (Economic and Political Thought, 2023)
Migration is a natural phenomenon, as old as the human species itself. Mov- ing from one place to another is a challenging, even painful situation for the migrants, but it also leads to an exchange of experiences among various peoples, which contributes to the improvement of our everyday life and the adoption of better laws and institutions. Nowadays, the West in general and Europe in particular are experiencing a new phenomenon of illegal immigra- tion over which it exercises less and less control. Treating it as a new human right, on the one hand, and avoiding confrontation with reality by state governments, on the other, may lead to deplorable consequences, i.e., it could result in a new “Migration Period”, reminiscent of one that occurred in late antiquity and that terminated the Western Roman Empire.